Ovarian carcinosarcoma associated with serous tubal intraepithelial carcinoma - Asencio Aguedo, Angélica Yeyli (2023)
Primary ovarian carcinosarcoma is a low incidence neoplasm that is usually diagnosedin advanced stages and has a poor prognosis. We report the case of a 64-yearoldfemale patient with a 15 cm abdominopelvic tumor. Histological examinationrevealed a malignant ovarian biphasic malignancy associated with a serous tubalintraepithelialcarcinoma, a finding that would be related to the pathogenesis of thisneoplasm.